Dimensions and Gaps of Social Support for Type 2 Diabetes Mellitus Patients in a Rural Prolanis Setting: A Qualitative Study - Arrum Firda Ayu Maqfiroch; Elviera Gamelia; Windri Lesmana Rubai; Ifa Najiyati; Siti Masfiah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2026)
ABSTRACT Background: Type 2 diabetes mellitus is a major public health burden in Indonesia, with Central Java reporting a prevalence higher than the national average. Beyond metabolic complications, patients often face psychological burdens and social constraints that influence the capacity for effective self management. Social support was widely recognized as a determinant of diabetes outcomes. Therefore, this study aimed to explore the dimensions and gaps of social support among type 2 diabetes patients enrolled in the Prolanis program at Cilongok I PHC. Methods: A phenomenological method was adopted, and data were collected through in-depth interviews with purposively selected patients, transcribed verbatim, and analyzed thematically to identify patterns across patient, family, and healthcare worker perspectives. Results: Four dimensions of social support were identified, namely emotional, appraisal, instrumental, and informational support. Emotional support was commonly expressed through empathy and encouragement, but remained normative, lacking psychological depth and safe spaces for patients to articulate fear or distress. Appraisal support was limited to clinical feedback, with no structured mechanisms for patients to provide input and low confidence to voice concerns. Instrumental support was present through routine services and transportation assistance, but it was constrained by long waiting times, physical discomfort during procedures, limited family accompaniment, and financial as well as geographic barriers. Informational support was conveyed through brief counseling and WhatsApp reminders. However, educational activities were inconsistent, predominantly administrative, and occasionally countered by misinformation from peers. Keywords : Social support Diabetes mellitus type 2 Prolanis Rural primary care